Parametric study of laser cutting of carbon fibre reinforced polymer (CFRP) and the effect of fibre orientation on cutting quality. Issue 2 (3rd April 2019) - Raza, Mohammad Shahid; Datta, Susmita; Bule, Bhupendra; Saha, Partha
ABSTRACT: Laser cutting of CFRP was performed using 2 kW fibre laser. A detailed analysis of the effect of various laser processing parameters on the cutting of CFRP was carried out. The present work considers mainly laser power (W), scan speed (mm/min), gas pressure (bar) and duty cycle (%) as the process parameters with average kerf width and heat affected zone (HAZ) as the output parameters. Cutting of the fibres at 90º with respect to fibre orientation was performed. The SEM and EDS analysis were also performed to understand the cut quality, matrix melting, fibre pullout and vaporisation phenomena of the matrix in the heat affected zone (HAZ). Laser cutting of CFRP with a minimum kerf width of around 184 µm was observed for 800 W, 600 mm/min, 3 bar and 25% duty cycle while HAZ in this parameter was around 1561 µm. Kerf width and HAZ directly increase with an increase in laser power, gas pressure and duty cycle, but they reduce with increase in scan speed. SEM images confirm that the CFRP cutting process generates relatively burr-free fibre edges. Matrix recession and delamination (fibre pullout) were identified as the major quality defects occurring in the laser cutting process of CFRP.